Islamic Boarding Schools as Agents of Sustainable Development: A Social Innovation Perspective from Darussalam Blokagung - Fitdarus Kussuma (Journal of General Education and Humanities, 2026)
Traditional Islamic boarding schools (pesantren) in Indonesia hold deep-rooted social capital and community trust, yet their potential as institutional actors for sustainable development remains underexplored, particularly within the framework of social innovation theory and the SDGs agenda. As global challenges such as climate change, economic inequality, and ecological degradation intensify, there is a growing need to understand how faith-based educational institutions can serve as strategic agents of transformative change. This study aims to identify and analyze the role of Darussalam Blokagung Islamic Boarding School in adopting social innovation as a strategy for local-to-global sustainable development aligned with the SDGs. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation involving 15 purposively selected participants, comprising boarding school administrators, senior students, local community members, and institutional partners. Data were analyzed using the Miles and Huberman interactive model, with triangulation applied to ensure credibility and validity. The findings reveal three interlocking mechanisms: (1) the visionary and transformative leadership of Kiai Dr. KH. Ahmad Munib Syafa'at as the primary catalyst for innovation; (2) multi-sector collaboration with universities, government agencies, and NGOs that expands the school's social reach; and (3) ecological initiatives — including reforestation programs and waste banks — that institutionalize environmental responsibility within the pesantren culture. This study contributes theoretically by integrating Islamic educational leadership with SDG-based social innovation, offering a holistic framework that bridges local Islamic wisdom with global sustainability agendas — an integration absent from previous studies that addressed these dimensions only partially. In practice, the findings recommend collaborative policies among pesantren, the government, and NGOs, as well as the integration of green curricula into national Islamic boarding school education standards.